Flanking SSR markers for alleles involved in the necrosis of hybrids between hexaploid bread wheat and synthetic hexaploid wheat. Issue 6 (2nd November 2017) - Kandel, D. R.; Glover, K. D.; Berzonsky, W. A.; Gonzalez-Hernandez, J. L.; Ali, S.; Chao, S.; Bhusal, S. J.
ABSTRACT: Hybrid necrosis in wheat ( Triticum aestivum L.) is the premature death of leaves or plants caused by the interaction of two dominant complementary genes, Ne1 and Ne2, located on chromosomes 5B and 2B, respectively. We examined allelic interaction effects of necrosis alleles using simple sequence repeat (SSR) markers in F2 populations derived from crossing the cultivar "Alsen" with a synthetic hexaploid "TA4152-37". The SSR marker Xbarc7 was linked at a distance of 3 cM to the quantitative trait loci (QTL) located on chromosome 2B, and Xgwm639 was 11 cM from the 5B QTL. A significant additive by additive epistatic interaction was detected between Ne1 and Ne2 QTL, and the results suggest that Alsen possesses a moderate necrosis allele, Ne2 m ; whereas, TA4152-37 possesses a moderate necrosis allele, Ne1 m . The Ne2 m allele had a stronger effect than the Ne1 m allele, and a total of 94.6% of phenotypic variance was explained by these genes and their interactions. This demonstrates the strong phenotypic effect due to even moderate necrosis alleles, and emphasizes the need for breeders to accurately predict and identify hybrids that will result in necrosis.